2012
DOI: 10.1136/bcr.12.2011.5383
|View full text |Cite
|
Sign up to set email alerts
|

Acute life-threatening methaemoglobinaemia following ingestion of chloroquine

Abstract: A 25 year old man was rushed to the emergency department when he was found unconscious in his room after taking two chloroquine tablets (600 mg base) for fever prescribed by local practitioner. On examination, the patient was unconscious and deep cyanosis was present on lips, tongue, oral cavity, nail beds and finger tips. Subsequent laboratory investigation revealed methaemoglobin level of 54%. Diagnosis of chloroquine-induced methaemoglobinaemia was made and methylene blue (1 mg/kg) was administered. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Carboxyhemoglobinemia, which leads to overestimates of the arterial oxygen saturation, could conceivably be seen in individuals with heavy tobacco use or who are using gas grills or heaters in enclosed spaces. Methemoglobin is less likely to be seen in the general population, although some drugs, including chloroquine ( 21 ) and antibacterial sulfonamides like dapsone ( 22 ), can be problematic. However, the typical values measured by these devices when methemoglobin levels become clinically important always fall below <90% and would fortunately lead patients to present to care by any reasonable threshold of apparent developing hypoxemia.…”
Section: Sources Of Error In Pulse Oximetry Monitoringmentioning
confidence: 99%
“…Carboxyhemoglobinemia, which leads to overestimates of the arterial oxygen saturation, could conceivably be seen in individuals with heavy tobacco use or who are using gas grills or heaters in enclosed spaces. Methemoglobin is less likely to be seen in the general population, although some drugs, including chloroquine ( 21 ) and antibacterial sulfonamides like dapsone ( 22 ), can be problematic. However, the typical values measured by these devices when methemoglobin levels become clinically important always fall below <90% and would fortunately lead patients to present to care by any reasonable threshold of apparent developing hypoxemia.…”
Section: Sources Of Error In Pulse Oximetry Monitoringmentioning
confidence: 99%
“…Methaemoglobinaemia should be suspected based on the clinical history, physical examination and on discrepancy between the oxygen saturation obtained by routine pulse oximetry and the oxygen saturation calculated from arterial blood gas analysis—‘saturation gap’ 2 3. In this case, a thorough physical examination raised the suspicion of methaemoglobinaemia and the patient was treated accordingly in a short time frame despite the fact that the partial pressure of arterial oxygen (PaO 2 ) could not be determined, as previously mentioned.…”
Section: Discussionmentioning
confidence: 95%
“…Trials have demonstrated some benefits for use in sepsis in critical care settings,11 although the largest dedicated trial for its use in sepsis (SMURF trial) was recently withdrawn prior to enrolment 12. Methylene blue is used in the treatment of methaemaglobinaemia and overdose of other agents through different mechanisms 13. There are also early experimental data to suggest that it may  be a potential neuroprotective agent 14…”
Section: Discussionmentioning
confidence: 99%